ANALISIS SULTHAH QADHAIYYAH TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NO. 36/PUU-XV/2017 TERKAIT KEDUDUKAN KOMISI PEMBERANTASAN KORUPSI - Asmarianti Asmarianti; Sri Yunarti (Institut Agama Islam Negeri Batusangkar, 2022)
This study examines the analysis of Sultah Qadhaiyyah against the Constitutional Court Decision No. 36/PUU-XV/2017 concerning the Position of the Corruption Eradication Commission. This study wants to find answers about the position of the Corruption Eradication Commission in the Indonesian government system and how Sulthah Qadhaiyyah's perspective on the decision of the Constitutional Court No. 36/ PUU-XV/2017 regarding the position of the Corruption Eradication Commission. This research is a library research, namely literature research which is excavated based on the main sources (data) systematically and analyzed from the collected material which is carried out qualitatively, which means identifying, compiling, managing and describing systematically, then analysis is carried out. by describing a systematic interpretation. The results of this study found that the position of the KPK in the Indonesian government system is an institution that is in the realm of the executive, as stated in Article 1 paragraph (3) of Law No. 19 of 2019 concerning the second amendment to Law no. 30 of 2002 concerning the Corruption Eradication Commission. Sulthah Qadhaiyyah's perspective on the decision of the Constitutional Court no. 36/ PUU-XV/2017 regarding the position of the Corruption Eradication Commission that the KPK institution is in the wilayatul mazalim judiciary which is under the auspices of Sulthah Qadhaiyyah (judicial institution).